Cytological and molecular aspects of the ageing sperm. Issue 2 (14th December 2018) - Paoli, Donatella; Pecora, Giulia; Pallotti, Francesco; Faja, Fabiana; Pelloni, Marianna; Lenzi, Andrea; Lombardo, Francesco
Abstract: STUDY QUESTION: Is ageing associated with a decline in semen quality and molecular changes to human sperm? SUMMARY ANSWER: Semen quality declines with advancing age and characteristic molecular changes take place during the ageing process, including increased sperm DNA damage, altered sperm protamination and altered seminal plasma miRNA profile. WHAT IS KNOWN ALREADY: During ageing, the reproductive system is exposed to physiological changes and potentially damaging factors that may impair testicular function. Reactive oxygen species (ROS) can induce errors during DNA replication, transcription or post-transcriptional events (fragmentation, chromatin condensation abnormalities and protamine expression defects). STUDY DESIGN, SIZE, DURATION: Semen parameters from 2626 healthy men aged 20–81 years were evaluated retrospectively from those attending our University Laboratory between 2011 and 2016 for andrological screening or as part of an andrological work-up. Subjects were divided into six groups by age (20–32, 33–37, 38–40, 41–44, 45–50, 51–81 years). From these subjects, semen samples from 40 elderly men (50–81 years) and 40 young men (20–40 years) (control group), all non-smokers of normal weight, were selected for the evaluation of sperm chromatin integrity, PRM1, PRM2, TNP1 and TNP2 gene expression, and microRNA expression profile in seminal plasma. PARTICIPANTS/MATERIALS, SETTING, METHODS: Semen was analysed according to WHO 2010. Sperm DNA fragmentation (SDF) was evaluated using TUNEL assay; sperm PRM1, PRM2, TNP1 and TNP2 gene expression was evaluated by quantitative RT-PCR amplification; miRNA expression profiles were analysed by TaqMan Array Cards and validated by RT-PCR amplification. MAIN RESULTS AND THE ROLE OF CHANCE: Cytological analysis – Semen volume, progressive motility and number of progressively motile sperm were significantly lower in elderly than in younger subjects (sextiles 51–81 versus 20–32 years; P < 0.001), while the percentage of abnormal forms in these subjects was significantly higher than in the 20–32 age group ( P = 0.002). Binomial logistic regression models revealed an association between age and semen parameters: age 51–81 was associated with changes in total sperm number (OR 2.47; 95% CI 1.52–4.02; P < 0.001), progressive motility (OR 3.63; 95% CI 2.49–5.30; P < 0.001), and abnormal forms (OR 3.89; 95% CI 2.71–7.26; P < 0.001). Obesity was associated with reduced progressive motility (OR 1.58; 95% CI 1.14–2.19; P = 0.006) and an increase in abnormal forms (OR 1.87; 95% CI 1.02–3.57; P = 0.021). In contrast, smoking did not contribute significantly to changes in semen parameters. Molecular analysis – Elderly men showed a significantly higher percentage of SDF (23.1 ± 8.7 versus 9.8 ± 2.6%; P < 0.001) and a significantly lower expression of PRM1 (mean fold change 2.2; P = 0.016) and PRM2 (mean fold change 4.6; P < 0.001), compared to younger controls. Furthermore, miR-146a showed a 3-fold lower expression ( P < 0.001), miR-371 a 14-fold lower expression ( P < 0.001), and miR-122 a 5-fold lower expression ( P = 0.01) in the elderly men. LIMITATIONS, REASONS FOR CAUTION: While typical chronic age-related conditions (cardiovascular, respiratory diseases) were excluded, the presence of subclinical underlying diseases cannot be excluded in the elderly population. Subjects referred to our clinic might not be fully representative of the general population. Although a careful medical history and physical examination excluded most andrological conditions that might affect spermatogenesis, we cannot exclude the presence of possible asymptomatic or idiopathic conditions. Furthermore, TUNEL, in common with other SDF detection methods (with the exception of the alkaline comet assay), does not distinguish between single and double strand breaks. WIDER IMPLICATIONS OF THE FINDINGS: The role of obesity suggests that conditions related to lifestyle factors may further worsen age-related sperm parameter impairment. Increased SDF and altered protamine expression suggest the genomic fragility of sperm in advanced age. Changes in the miRNA expression pattern with age could contribute to the identification of a characteristic molecular signature of the ageing process, a potential new biomarker for male reproductive function during the physiological ageing process. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a grant from the Italian Ministry of Education and Research (MIUR-PRIN 2015- 2015XSNA83-002) and 'Sapienza' University of Rome Faculty of Medicine. The authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A